Construction and validation of a prediction model of extrahepatic metastasis for hepatocellular carcinoma based on common clinically available data - Zhou, Lliuxin; Zhou, Liuxin; Ren, Li; Qi, Mengjian; Wang, Wen; Su, Xiaoxia; Yin, Fengjiao; Deng, Manjun; Wang, Haijiu; Fan, Haining; Wang, Zhixin (Frontiers in Oncology, 2022)
Objective This study aimed to investigate the clinical characteristics and risk factors of patients with hepatocellular carcinoma (HCC) with extrahepatic metastases (EHM) and to establish an effective predictive nomogram. Methods Clinical and pathological data from 607 patients with hepatocellular carcinoma admitted to the Affiliated Hospital of Qinghai University between 1 January 2015 and 31 May 2018 were documented, as well as demographics, clinical pathological characteristics, and tumor-related parameters to clarify clinical risk factors for HCC EHM. These risks were selected to build an R-based clinical prediction model. The predictive accuracy and discriminating ability of the model were determined by the concordance index (C-index) and the calibration curve. The results were validated with a bootstrap resample and 151 patients from 1 June 2018 to 31 December 2019 at the same facility. Results In multivariate analysis, independent factors for EHM were neutrophils, prothrombin time, tumor number, and size, all of which were selected in the model. The C-index in the EHM prediction model was 0.672 and in the validation cohort was 0.694. In the training cohort and the validation cohort, the calibration curve for the probability of EHM showed good agreement between the nomogram prediction and the actual observation. Conclusion The extrahepatic metastasis prediction model of hepatocellular carcinoma constructed in this study has some evaluation capability.